Epistatic evidence for gender-dependant slow neurotransmission signalling in substance use disorders: PPP1R12B versus PPP1R1B - Liu, Kefu; Zhao, Juan; Chen, Chunnuan; Xu, Jie; Bell, Richard L; Hall, Frank S; Koob, George F; Volkow, Nora D; Qing, Hong; Lin, Zhicheng (EBioMedicine, 2020)
BACKGROUND: Slow neurotransmission including DARPP-32 signalling is implicated in substance use disorders (SUDs) by experimental systems but not yet in the human aetiology. PPP1R12B, encoding another protein in the DARPP-32 family, hasn't been studied in the brain. METHODS: Brain-regional gene activity was assessed in three different animal models of SUDs for mRNA level alterations. Genetic associations were assessed by meta-analysis of pre-existing dbGaP GWAS datasets for main effects and epistasis with known genetic risks, followed by cell type-specific pathway delineation. Parkinson's disease (PD) was included as a dopamine-related disease control for SUDs. FINDINGS: In animal models of SUDs, environmentally-altered PPP1R12B expression sex-dependently involves motivation-related brain regions. In humans with polysubstance abuse, meta-analysis of pre-existing datasets revealed that PPP1R12B and PPP1R1B, although expressed in dopamine vs. dopamine-recipient neurons, exerted similar interactions with known genetic risks such as ACTR1B and DRD2 in men but with ADH1B, HGFAC and DRD3 in women. These interactions reached genome-wide significances (Pmeta<10-20) for SUDs but not for PD (disease selectivity: P = 4.8 × 10-142, OR = 6.7 for PPP1R12B; P = 8.0 × 10-8, OR = 2.1 for PPP1R1B). CADM2 was the common risk in the molecular signalling regardless of gender and cell type. INTERPRETATION: Gender-dependant slow neurotransmission may convey both genetic and environmental vulnerabilities selectively to SUDs. FUNDING: Grants from National Institute on Drug Abuse (NIDA) and National Institute on Alcohol Abuse and Alcoholism (NIAAA) of U.S.A. and National Natural Science Foundation of China (NSFC).
Keywords: mozek; náchylnost k nemoci; dopaminem a cAMP regulovaný fosfoprotein 32; myši; genetická epistáze; krysa rodu Rattus; mužské pohlaví; Protein Phosphatase 1; Sex Factors; Synaptic Transmission; genetická predispozice k nemoci; nervový přenos; Dopamine and cAMP-Regulated Phosphoprotein 32; Male; poruchy spojené s užíváním psychoaktivních látek; Female; Humans; regulace genové exprese; Gene Regulatory Networks; Brain; Genetic Predisposition to Disease; lidé; proteinfosfatasa 1; ženské pohlaví; modely nemocí na zvířatech; Rats; Genetic Heterogeneity; Genome-Wide Association Study; Organ Specificity; Animals; sexuální faktory; Disease Susceptibility; zvířata; Mice; celogenomová asociační studie; orgánová specificita; genetická heterogenita; Substance-Related Disorders; genové regulační sítě; Disease Models, Animal; Epistasis, Genetic; Gene Expression Regulation